A GLANCE OF I4.0 AT SUPPLY CHAIN AND INVENTORY MANAGEMENT - Avilés-Sacoto, Sonia Valeria; Avilés-González, Jonnatan Fernando; Garcia-Reyes, Heriberto; Bermeo-Samaniego, Maria Cristina; Cañizares-Jaramillo, Ana Katherin; Izquierdo-Flores, Sofia Natalia (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
During last years, organizations are facing strong forces of competition due to market uncertainty, international competition, highly demand on personalized products and services, among other factors. One of the initiatives proposed to deal with this threat is the Industry 4.0 transformation, also known as smart manufacturing or Industrial Internet of Things. However, adoption of Industry 4.0 initiatives is not so easy due to challenges related to technological adoption issues, data-driven process and cultural behavior. Supply chain operations are not exempt to be impacted by the current market situations. For example, inventory management is challenged by the reduction on the product life cycle and production flexibility required to meet the customer demand. This article presents a literature review of how the Industry 4.0 is affecting supply chain operations and inventory management fields, based on three research questions to explore the state of the art of the topic. Findings show a fertile field for new methods and operations supported by technology and data-driven operations in order to become an Industry 4.0 adopter. To this end, a list of twelve technologies and its impact to the supply chain and manufacturing operations are provided. However, there are some challenges such that all the organization are not ready to start its adoption, thus future work will be focus in the development of a new roadmap models to attain these challenges mainly for SMEs organizations.